Relationship of Helicobacter pylori vacA i1 and i2 alleles with gastric cancer risk, Iran: brief report - Batool Mottaghi (Tehran University Medical Journal, 2014)
Background: Helicobacter pylori vacA (vacuolating toxin A) gene is comprised of mid- (m), intermediate- (i) and signal-regions. Recently, the vacA-i region genotype has been suggested to be a better predictor of disease severity than either the s- or m-region. The main aim of the present study was to determine the associations of i region poly-morphisms of vacA gene with gastric cancer (GC) and peptic ulcer disease (PUD) in Azerbaijan Province patients. Methods: A number of 89 patients were enrolled. The biopsy samples were taken from patients referring to the endoscopy units of Imam Reza and Shahid Madani Hospitals, Tabriz, Iran from August 2012 to May 2013. The genotype frequencies of vacA-i1 and i2 in were studied using polymerase chain reaction (PCR). Results: The frequency of vacA-i1 and i2 was 51.68% and 48.31%, respectively. The genotypic frequency of vacA-i1 in patients with GC (21/24, 87.5%) was significantly higher than in those with non-atrophic gastritis, NAG (19/48, 39.58%). In contrast, the genotypic frequency of vacA-i2 in patients with NAG, PUD, and GC was 60.42%, 64.70%, and 14.28%, respectively. The results of multiple linear and logistic regression analyses confirmed the intensity of correlation of vacA-i1 allele with GC compared with control group (NAG). No significant correlation was found between the vacA-i-region alleles and PUD risk. Conclusion: We have proposed that the H. pylori vacA-i1 genotype could be an im-portant biomarker for predicting the gastric cancer risk in Azerbaijan Province in Iran. However, due to the difference in the allelic frequency of this gene in H. pylori strains from different parts of the world, the vacA-i1 genotype usefulness in predicting the gas-trointestinal diseases is dependent to the geographic origin of the strains.